PENERAPAN PROBLEM BASED LEARNING PADA MATERI PENCEMARAN LINGKUNGAN UNTUK MENINGKATKAN KEMAMPUAN ARGUMENTASI ILMIAH TERTULIS SISWA KELAS X MIPA - Rahmad Anung Prasetya Wibawa (Program Studi Pendidikan Biologi, 2018)
ABSTRACT The research aims to improve students written scientific argumentation through the application of problem based learning into enviromental pollution main subject at class X Science. The research was a Classroom Action Research (CAR). It was carried out in two cycles in which each cycle consists of four stages: planning, action, observation, and reflection. The subject of the research was 38 students of X Science.The source of the data came from teacher and students. Technique of collecting data used tests, interviews, and documentation. The main data about students written scientific argumentation covers three aspects, they are: claim, evidence, and reasoning. The technique used to validate this data was triangulation method. The data was analyzed using descriptive analysis technique. The research procedure used eas the spiral method. The reasearch target was improvement of written scientific argumentation increase ≥30% from base line.The result showed the application of problem based learning can improve written scientific argumentation students at class X Science. Percentage performance students written scientific argumentation in pre-action is 36,55% with a low category, consists of claim at 50,88% with a medium category, evidence at 35,09% with a low category; and reasoning at 23,68% with a low category. Percentage performance students written scientific argumentation in the first cycle increased to 57,89% with a medium category, consists of claim at 64,91% with a high category, evidence at 56,14% with a medium category; and reasoning at 52,63% with a medium category. Percentage performance students written scientific argumentation in the second cycle increased to 86,55% with a very high category, consists of claim at 97,37% with a very high category, evidence at 85,97% with a very high category; and reasoning at 76,31% with a high category. Data increase written scientific argumentation from pre-action to second cycle has been increased according to the target is ≥30%. Key Words:written scientific argumentation, problem based learning, enviromental pollution.